Corrigendum to “Combined effects of dietary low molecular weight sodium alginate and Pediococcus acidilactici MA18/5M on growth performance, haematologicaland innate immune responses of Asian sea bass (Lates calcalifer) juveniles” [FSI 79 (2018) 34–41](S1050464818302687)(10.1016/j.fsi.2018.05.011) - Ghasem Ashouri (2019)
© 2019 Elsevier Ltd Corrigendum to “Combined effects of dietary low molecular weight sodium alginate and Pediococcus acidilactici MA18/5M on growth performance, haematological and innate immune responses of Asian sea bass (Lates calcalifer) juveniles” [Fish and Shellfish Immunology 79 (2018) 34–41]. The authors would like to declare that there was a mistake in affiliations of the first, 2nd and 4th authors which should be corrected as “Department of Natural Resources (Fisheries Division), Isfahan University of Technology, Isfahan 84156-83111, Iran”. The authors would like to apologies for any inconvenience caused.